Novel homo- and heterobinuclear ball-type phthalocyanines: synthesis and electrochemical, electrical, EPR and MCD spectral properties - ÖZKAYA, ALİ RIZA; DUMLUDAĞ, FATİH; ODABAŞ, ZAFER (ROYAL SOC CHEMISTRY, 2010)
The mononuclear Fe(II) phthalocyanine 2 and ball-type homobinuclear Fe(II)-Fe(II) and Cu(II)-Cu(II) phthalocyanines, 3 and 4 respectively, were synthesized from the corresponding 4,4'-[1,1'-methylenebis-(naphthalene-2,1-diyl)]bis(oxy)diphthalonitrile 1, and then ball-type heterobinuclear Fe(II)-Cu(II) phthalocyanine 5 was synthesized from 2. The novel compounds 4 and 5 have been characterized by elemental analysis, UV/vis, IR and MALDI-TOF mass spectroscopies. Electron paramagnetic resonance and magnetic circular dichroism measurements of 3, 4 and 5 were also examined. The voltammetric measurements of the complexes showed the formation of various electrochemically stable ligand-and metal-based mixed-valence species, due to the intramolecular interactions between the two MPc units, especially in ball-type binuclear iron(II) phthalocyanine. Impedance spectroscopy and d.c. conductivity measurements of 4 and 5 were performed as a function of temperature (295-523 K) and frequency (40-10(5) Hz). While room temperature impedance spectra consist of a curved line, a transformation into a full semicircle with increasing temperature was observed for both compounds.
Keywords: GAS-SENSING PROPERTIES; HETERO-DINUCLEAR PHTHALOCYANINES; MAGNETIC CIRCULAR-DICHROISM; COPPER-PHTHALOCYANINE; OXYGEN REDUCTION; THIN-FILMS; METAL-FREE; BINUCLEAR; METALLOPHTHALOCYANINES; COBALT(II)